Optical mesoscopy without the scatter: broadband multispectral optoacoustic mesoscopy - Chekkoury, Andrei (Biomed Opt Express, 2015)
Optical mesoscopy extends the capabilities of biological visualization beyond the limited penetration depth achieved by microscopy. However, imaging of opaque organisms or tissues larger than a few hundred micrometers requires invasive tissue sectioning or chemical treatment of the specimen for clearing photon scattering, an invasive process that is regardless limited with depth. We developed previously unreported broadband optoacoustic mesoscopy as a tomographic modality to enable imaging of optical contrast through several millimeters of tissue, without the need for chemical treatment of tissues. We show that the unique combination of three-dimensional projections over a broad 500 kHz–40 MHz frequency range combined with multi-wavelength illumination is necessary to render broadband multispectral optoacoustic mesoscopy (2B-MSOM) superior to previous optical or optoacoustic mesoscopy implementations.